Socialization of Islamic Banks Versus Conventional Bank Products: Increasing Knowledge of Santri in Pesantren Nurul Ummah Yogyakarta - Shinta Shafa Arwidia; Tyas Ayu Rahmita; Alya Laili Utdkhiati; Silvia Amelia Ardani; Asa Usio; M Anwar Sadid; Wildan Kurnia Hasan; Althaf Daffadhila; Ibnul Mubarok; M Joan Ariqa (Journal of Islamic Economy and Community Engagement, 2022)
The practice of usury carried out by several banks became anxious for some people who have a high religious level. Therefore, Islamic banks are established to become institutions for raising funds and financing for the people using sharia principles. But at this time literacy about Islamic banks is still minimal among the public. To increase literacy on Islamic banks in the community, socialization activities on Islamic banks were conducted to the public. The socialization activities were carried out at the Nurul Ummah Islamic Boarding School Student Dormitory. Material for socialization on management of the Islamic banking system with conventional banking. The socialization material was delivered in the form of powerpoints with the support of facilities and infrastructure including; laptops, projectors, screens and consumption. The result, participants of the socialization understand the differences between the management of Islamic banks and conventional banks.Keywords: Counseling, Islamic Banks, Conventional Banks